Wczesnochrześcijańskie rozważania o imieniu Jezus - Paczkowski, Mieczysław Celestyn (Poznańskie Studia Teologiczne, 2018)
This study opens with a brief reflection on the typological value of the person and name of Josh- ua in the ancient Church. Christians saw the figure of Joshua as a foreshadowing of the saving work of Jesus Christ. According to patristic vision the order of grace in Jesus Saviour replaces the ancient order of the Law. On the basis of homonymy Joshua is associated with Christ. The intent of the study was also to present the historical beginning of the practice to invocate the Lord’s Name. To express the faith in Christ symbolically, the first Christians recurred to the use of numerology and to the nomina sacra. This article argues that the ancient Christian literature contains sustained and substantial references to the name of Jesus as ‘Saviour’. It is possible to find the theological finality in the interpretation of Lord’s name. At every point of the discussion in the Patristic tradition it is found a considerable richness and significance of the name of Jesus (biblical, doctrinal and spiritual).